1995
DOI: 10.1002/gps.930101204
|View full text |Cite
|
Sign up to set email alerts
|

Citation patterns in the International Journal of Geriatric Psychiatry: Cultural ethnocentrism revisited?

Abstract: The country/region of origin of all original papers appearing in the Znternarional Journal of Psychiatry (IJGP) during the first 9 years of its publication was recorded. A more detailed analysis of citation patterns was carried out on the 105 original articles published during 1992. The results indicated that 50-60% of the articles emanated from the United Kingdom but that in general authors cited a broad range of specialities from journals published around the world. North American authors tended to cite Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Second, the practice of targeted self-citation is contentious, as it can be used to boost impact. Within some psychiatric subspecialties, it has been suggested that US authors disproportionately self-cite and cite colleagues from US institutions [ 23 , 24 ], a trend also reported in the wider scientific literature [ 25 ]. Furthermore, in general medicine [ 26 ] and in some specialties [ 27 ] it has been shown that US authors cite UK authors less often than UK authors cite US authors.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the practice of targeted self-citation is contentious, as it can be used to boost impact. Within some psychiatric subspecialties, it has been suggested that US authors disproportionately self-cite and cite colleagues from US institutions [ 23 , 24 ], a trend also reported in the wider scientific literature [ 25 ]. Furthermore, in general medicine [ 26 ] and in some specialties [ 27 ] it has been shown that US authors cite UK authors less often than UK authors cite US authors.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriation of the concept in the context of informational disciplines has opened the possibility of new studies to characterize phenomena inherent to librarianship and scientific information systems. Citations between disciplines or editorial endogamy, to cite two examples identified in scientific production (Barak, Philpot & Levy, 1995), are aspects addressed relatively frequently in Information Science. The ethnocentricity associated with these phenomena could be implicit in many other studies that analyze patents (Silva et al, 2014), conference proceedings (Montolio, Dominguez-Sal, & Larriba-Pey, 2013), or collaborative networks (Miranda Grochocki & Cabello, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…From a quantitative perspective, beyond the bibliometric explorations mentioned in the introduction of this article, it was identified how the appropriation of the concept of "ethnocentricity" in the field of Library and Information Science has also been associated with the study of very specific topics, such as the usability of collections in a library (McGrath, Simon & Bullard, 1979), and the levels of inbreeding in authorship and citation patterns of scientific journals (Barak, Philpot, & Levy, 1995). In general, these results show not only the conceptual appropriation but also the need to adapt it within the discipline itself to understand individual and social behaviors in the management of institutional processes and the publishing ecosystem.…”
Section: Original Articlementioning
confidence: 99%
“…Problems and solutions constructed using the index study have been The distribution of the second-order citations is quite clear-US-based authors tend to cite other US-based authors, which is a known phenomenon from other bibliometric studies. [78][79][80][81] This has been linked to boosting the impact 82 and intellectual orientation of the United States and international researchers towards a particular, dominant US problem representation. 78 The result is that the | 587…”
Section: Problem Representations Are Disseminated Unequallymentioning
confidence: 99%